Diseño de una red de telemetría para gestión del sistema de alumbrado público del área de regeneración urbana de la ciudad de Loja - Romero Carrión, Bryan Armando (2019)
This article provides a technical proposal that ensures the good performance of the network telemanagement that accompanies the new public lighting system in the area that will complement to the " Proyecto de Regeneración Urbana de la ciudad de Loja". Starting with a brief analysis of the current state of public lighting system let's maintain the bases to start with the construction of the proposal, continue with the bibliographic review of wireless sensor networks, ZigBee, telemanagement and fiber optics. It is known that the contract provides inter alia, the deployment of the lighting system for the intervention area of urban regeneration is carried out using the Brand Schréder, under the supervision of “Empresa Eléctrica Regional del Sur S.A.- EERSSA”, that is why the different analysis were carried out based on commercial values of the devices with which the brand works. Computer tools such as MATLAB, Riverbed Modeler, AirView, NetSpot and AutoCAD were necessary to define a solid proposal, which is detailed throughout the last chapter.